An axiological dimension of Qur’ānic epistemology - Solihu, Abdul Kabir Hussain (African Journals Online (AJOL), 2014)
This study inquires into the value system associated with two epistemological conceptual schemes of the Qur’ān, namely, āyah (sign) and ḥikmah (wisdom). In many respects, the rapid accumulation of all types of knowledge and the progress in the predominantly secular science and technology of modern times have marginalised values from scientific inquiry, leading to intellectual crisis, epistemological confusion and social disorientation. Thus, there is a clarion call to revisit the place of values in epistemological discourse. In an attempt to broaden the human horizon, the Qur’ān propounds a unified system of knowledge and value whereby it draws attention to several natural phenomena seen as āyāt (signs) of Allah which should be explored through a ḥikmah-based framework of value judgment. Guided by axiological concern, this study examines the place of value in Qur’ānic epistemology.